Effects of methanol extracts of insulin leaves (Tithonia diversifolia (hemsl.) A. Gray) on insulin resistance and secretion of alloxan induced-obese diabetic rats - Raden Edi Fitriyanto; Sugiarto Sugiarto; Dwi Tonang Ardiyanto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Obesity can lead to insulin resistance contributing to diabetes mellitus (DM). Empirically, insulin leaves of Tithonia diversifolia (Hems.) A. Gray (Td) can be used as a traditional DM medicine.Objective: This study aims to determine effects of Td methanol extracts on insulin resistance and secretion in DM rats induced by a high-fat diet and alloxan.Methods: This study was a randomized pre and post-test control group. Its research subjects were divided into five groups: a normal group, an obese group with diabetes without therapy (KN), an obese group with DM treated by the Td extracts with a dose 50 mg/kg, 250 mg/kg, and 500 mg/kg. The DM obesity was induced by a high-fat diet followed by administration of alloxan with a dose of 135 mg/kg intraperitoneally. The Td extracts was administered after 7 days of DM induction by using gastric swabs. Insulin resistance in the rats was measured based on HOMA-IR index values, while their insulin secretion was based on HOMA-B values. A statistical analysis was conducted by a 95% confidence level.Results: Blood glucose levels decreased to normal levels in all the groups administered by the Td extracts, except in the KN group. The HOMA-IR index values in all groups treated by the Td extracts did not increase except in the KN group. The HOMA-B index values in groups with doses of 50 and 250 mg/kgBW experienced a higher increase and significantly differed with the KN group.Conclusion: The administration of the Td extracts with doses of 50 and 250 mg/ kgBW in the DM rats could decrease blood glucose levels, could prevent insulin resistance and could increase insulin secretion.